A dual two-level voltage source inverter for an open-end winding motor - Sahu Alok (Nanyang Technological University, 2022)
With the advent of transistors, that lead to Solid state switching capabilities gave rise various topologies in designing of an Inverter. This project focuses on Motor Control of an Open-ended Motor using two voltage source Inverters. The algorithm used is to generate references voltages for optimal speed control using Space vector Modulation scheme. The Machine is controlled by implementing FOC which is also thoroughly explained in the thesis. The model is implemented in SIMULINK-MATLAB. At the end of the paper the various use case analysis for different speed reference is done.